Power profiling in U23 professional cyclists during a competitive season - Leo, P.; Spragg, J.; Mujika, I.; Menz, V.; Lawley, J. S. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The aim of this study was to investigate changes in the power profile of U23 professional cyclists during a competitive season based on maximal mean power output (MMP) and derived critical power (CP) and work capacity above CP (W') obtained during training and racing.